Pengaruh Asap Cair Kayu Galam (Malaleuca leucadendra) dalam Bentuk Biodegradable Film terhadap Pengawetan Ikan Gabus (The Effect of Liquid Smoke Galam (Malaleuca leucadendra) in Biodegradable Film Form as Fish Cork Preservation) - Rais Salim; Nazarni Rahmi (Jurnal Riset Industri Hasil Hutan, 2017)
Liquid smoke is a liquid product made from the condensation of smoke from carbonization process of lignocellulosic material. Liquid smoke of wooden galam (Melaleuca leucadendra) is a material that can be used as a natural preservative on fish. The use of an edible film packaging with the addition of liquid smoke of wooden galam is a good alternative to improve the durability and quality of fish during storage. This research is aimed to determine the effect of liquid smoke of wooden galam in biodegradable film for fish preservation. The edible film formulas were gelatin-pectin (AB), gelatin-smoke liquid (AC), and gelatin-pectin-smoke liquid (ABC) and compared with control (without treatment). The parameters of fish storage observed were pH measurement, Total Volatile Base-Nitrogen (TVBN), and microbiological test. The result after 10 days of storage showed that the pH value were 5.45 incontrol, AB 5.43, AC 5.47 and ABC 5.46; theTVBN values were 48 mgN/100gin control, AB 32 mgN/100g, AC 36 mgN/100g and ABC 36 mgN/100g; as well as microbiological testing, TPC value on 15x106 CFU/g, AB 11x103 CFU/g, AC 18.5x103 CFU/g, and ABC 4x103 controls and Coliform controls 5.0x106, AB 3.5x102, AC 1.0x101, and ABC 4.0x100. The treatment of liquid wooden galam smoke in a form of biodegradable film was capable to maintain the quality of fish better than without treatment shown in the low microbiological testing values (TPC and Coliform), eventhough it did not show significant effect in maintaining the TVB value during 10 days storage at ± 4° C. Keywords:  liquid smoke, Coliform, edible film, pH, TPC